1979
DOI: 10.1128/jvi.29.1.242-249.1979
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of infectious transforming DNA by the avian sarcoma virus reverse transcriptase

Abstract: Infectious DNA molecules, capable of transforming chicken embryo fibroblasts, can be synthesized by the Rous sarcoma virus-associated reverse transcriptase in vitro. The optimal enzymatic conditions employed for infectious DNA synthesis also facilitate maximum synthesis of genome length DNA. Analysis of the DNA product synthesized by detergent-disrupted Rous sarcoma virus under these conditions indicates that DNA complementary to viral RNA (minus-strand DNA) is genome length in size, whereas DNA complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, it should be noted that Mn2+ rather than Mg2+ is the preferred divalent cation for murine leukemia virus reverse transcriptase (20, 44). In contrast, DNA synthesis by avian sarcoma virus (10) and EIAV (39) has been reported to lack sensitivity to high concentrations of divalent cation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that Mn2+ rather than Mg2+ is the preferred divalent cation for murine leukemia virus reverse transcriptase (20, 44). In contrast, DNA synthesis by avian sarcoma virus (10) and EIAV (39) has been reported to lack sensitivity to high concentrations of divalent cation.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the ability of permeabilized virions to synthesize a complete viral genome-length reverse transcript requires relatively high dNTP levels and careful titration of the reaction components, especially the detergent used to make the virion permeable (12,25,41,49). Although there have been reports of full-length intact duplex DNA being made in vitro (7,19), the vast majority of synthesized product contains an intact minus strand and a discontinuous positive strand (6,10,14,29,49), similar to the cytoplasmic forms detected early after infection (17,22,46,48). Other DNA forms have been detected as well, including branched structures and noncovalently closed circles (15,18,23,24).…”
mentioning
confidence: 99%
“…Our studies raise the question of the role of early viral proteins in the infectious cycle of retroviruses. Recent reports (6,29) demonstrated that viral cDNA prepared in vitro is infectious. However, the amount used in these experiments was severalfold higher than that anticipated to participate in a normal infection (about 100 equivalents of viral genome RNA, which equals about 5 x 10'4 pg [32]).…”
Section: --I F T -I ---mentioning
confidence: 99%
“…This may be due to a large excess of enzyme molecules present in reconstituted reactions, allowing an extensive action of RNase H in spite of nonoptimal conditions. DNA made in vitro in endogenous reactions can be largely converted into double-stranded and infectious forms (7,22,35). Since synthesis of the second DNA strand (plus strand) requires removal of the RNA in the RNA-DNA hybrid, a role of RNase H in the synthesis of plus-strand DNA has been postulated (27,31,32,46).…”
Section: Discussionmentioning
confidence: 99%